An Authoritative Source of Truth System for UCAV Conceptual Design - Xiaojian Sun; Mingqiang Luo; Zhiyang Cui; Zhicheng Zou; Hu Liu (IEEE Access, 2021)
Model-Based Systems Engineering (MBSE) is a part of a long-term trend toward model-centric approaches. The Authoritative Source of Truth (AST) is a crucial step of digital transformation and a core component of MBSE. Benefits include help design teams shorten the design cycle, improve design efficiency, and ensure the accuracy of design models and data compared to traditional document-based co-design methods. Data-driven design is a new direction of Unmanned Combat Aerial Vehicles (UCAV) design, and UCAV is the main force of future air warfare. How to build a UCAV conceptual design AST system is a problem that needs to be solved. We design an AST construction methodology, develop an AST system by applying the methodology, and use the UCAV concept design case to test the usability of the AST system. More specifically, the methodology includes construction goals and objects, basic construction methods, AST architecture, collaborative construction methods, dynamic management methods, basic functions and derivative tools required. In addition, the validation process is requirement analysis, functional architecture design, scheme design, and dynamic management validation. The AST system can help the implementation of MBSE in the field of aircraft design. The AST system can also help meet the requirements of the conceptual design stage, which shows the feasibility of the construction methodology’s integrity. If the AST system is used in the aircraft’s detailed design phase, further models and data will be required, and the AST system will need to be upgraded.